PENGARUH MODEL PEMBELAJARAN PQ4R BERBANTUAN MIND MAPPING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SEKOLAH DASAR - Rinellia Silvia; Muhammad Syahrul Rizal; Yenni Fitra Surya; Nurhaswinda; Mufarizuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading comprehension is a fundamental skill that elementary school students must develop. However, observational findings at Muhammadiyah Elementary School 014 Pulau Payung indicate that students' achievement in this area remains low. This study aims to examine the effect of the PQ4R learning model assisted by mind mapping on the reading comprehension ability of fifth-grade students. An experimental method was employed using a quasi-experimental design, specifically the nonequivalent control group design. The research sample consisted of class VA (26 students) as the experimental group and class VB (25 students) as the control group. The research instrument was a reading comprehension test. Data were collected through pretests and posttests and analyzed using normality tests, homogeneity tests, and independent sample t-tests. The results showed improvement in both groups, but the increase was significantly greater in the experimental class. The average pretest and posttest scores in the control class were 9.08 and 14.28, respectively, while those in the experimental class were 7.65 and 19.04. The data met the assumptions of normality and homogeneity, and the t-test revealed a significance value of less than 0.05, indicating a statistically significant difference between the two groups. It is concluded that the PQ4R model supported by mind mapping is effective in enhancing students’ reading comprehension skills across all measured indicators.